Relationship between Customer Satisfaction, Brand Trust and Customer Brand Loyalty - Khadijah, Kamisan (2010)
The main objective of this research is to determine the relationship between customer satisfaction, brand trust and customer brand loyalty among students who own computer. The data was collected from 201 students in Universiti Utara Malaysia through a self-administered questionnaire. The data was analysed using the Correlation and Regression test. The results show that there is a positive and significant relationship between both the independant variables, namely customer satisfaction and brand trust to customer brand loyalty. The more satisfied the customers with the brand they experience, the more loyal they are towards the brand. In addition, the more the customers trust the brand they are experiencing, the more loyal they tend to be towards the brand. The results also indicate that customer satisfaction contributed more significantly to the customer brand loyalty compared to brand trust.